COVID-19 in hematology: data from a hematologic and transplant unit (2020)
During the COVID-19 pandemic, special attention has been addressed in cancer care to mitigate the impact on the patient’s prognosis. We addressed our preparation to face COVID-19 pandemic in a Hematological and Stem Cell Transplant Unit in Brazil during the first two months of COVID-19 pandemic and described COVID-19 cases in patients and health care workers (HCW). Modifications in daily routines included a separation of area and professionals, SARS-CoV-2 screening protocols, and others. A total of 47 patients and 54 HCW were tested for COVID-19, by PCR-SARS-CoV-2. We report 11 cases of COVID-19 in hematological patients (including 2 post stem cell transplant) and 28 cases in HCW. Hematological cases were most severe or moderate and presented with several poor risk factors. Among HCW, COVID-19 were mostly mild, and all recovered without hospitalization. A cluster was observed among HCW. Despite a decrease in the number of procedures, the Transplant Program performed 8 autologous and 4 allogeneic SCT during the period, and 49 onco-hematological patients were admitted to continuing their treatments. Although we observed a high frequency of COVID-19 among patients and HCW, showing that SARS-CoV2 is disseminated in Brazil, hematological patients were safely treated during pandemic times